1978
DOI: 10.1111/j.1399-6576.1978.tb01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation in Unconscious Patients with Brain Injury

Abstract: In 18 unconscious patients with traumatic brain injury, the cerebral autoregulation was tested during the first 2-3 weeks after the acute trauma. Regional cerebral blood flow (rCBF) was measured by the intra-arterial 133xenon washout method before and after an increase of about 20% in the mean arterial blood pressure (MABP) by angiotensin. The difference between MABP and intraventricular pressure (IVP) was used as cerebral perfusion pressure (PP). Simultaneously, ventricular fluid pH, lactate and pyruvate were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 34 publications
3
32
0
2
Order By: Relevance
“…More generally, t displays a large variability in the patients of the autoregulated group, ranging from a few seconds to several 10ths of a second. The previous data confirm that autoregulation may be significantly altered in acute brain damage, a result reported by several authors (6,21). Differences between prompt and delayed autoregulation might be ascribed to damage of neural control pathways (which generally have time constants of a few seconds), which are possibly replaced by the action of slower metabolic or chemical feedback mechanisms (20).…”
Section: Discussionsupporting
confidence: 72%
“…More generally, t displays a large variability in the patients of the autoregulated group, ranging from a few seconds to several 10ths of a second. The previous data confirm that autoregulation may be significantly altered in acute brain damage, a result reported by several authors (6,21). Differences between prompt and delayed autoregulation might be ascribed to damage of neural control pathways (which generally have time constants of a few seconds), which are possibly replaced by the action of slower metabolic or chemical feedback mechanisms (20).…”
Section: Discussionsupporting
confidence: 72%
“…[6,9,21,22,25,26] Muizelaar and colleagues [21,22] evaluated autoregulation in head-injured patients by obtaining CBF values and either raising or lowering MABP to a new steady state and repeating the CBF measurement. They defined intact autoregulation as the •% CPP/ %• CVR ¾ 2 following the change in MABP, where CVR = CPP/CBF.…”
Section: Discussionmentioning
confidence: 99%
“…[14,26] Cerebral autoregulation can be impaired or absent following severe closed head injury. [4][5][6]8,9,21,22,25,26] Impairments in autoregulation may contribute by several mechanisms to secondary neuronal injury following head injury. Lowered cerebral perfusion pressure (CPP) caused by arterial hypotension or increased intracranial pressure (ICP) can occur and may cause critical reductions in cerebral blood flow (CBF) to ischemic levels more easily in head-injured patients who have poorly functioning or absent autoregulation.…”
mentioning
confidence: 99%
“…7,24 Some authors have suggested that cerebrovascular pressure reactivity could be derived from the characteristic pulse waveform from ABP, 26,27 although this has never been demonstrated to work in clinical practice. Perhaps changes in ABP are too fast (a fraction of a second) to mobilize an active vasoregulatory response.…”
mentioning
confidence: 99%